KONTRIBUSI GURU AGAMA ISLAM PADA SISWA UNTUK MEMBANTU KEGIATAN MEMBACA ALQURAN DI ANUBAN ISLAM SONGKHLA SCHOOL - Munawarah Munawarah; Selamat Pohan (Program Studi Pendidikan Biologi, 2022)
This study aims to determine the contribution of Islamic religion teachers to students in helping Al-Quran reading activities at Anuban Islam Songkhla School. This study used a descriptive qualitative method through field research (field research). The data in this study were obtained from various relevant sources, namely based on primary data sources and secondary data sources. In collecting the data, the researcher conducted semi-structured interviews and made observations on naturally occurring phenomena at Anuban Islam Songkhla School. The data that has been obtained will then be reduced, presented and concluded, these steps are an effort so that the research results that will be presented have credibility and can be objective. The results of this study indicate that the contribution of Islamic religious teachers at Anuban Islam Songkhla School refers to a number of manifestations of instilling Islamic values in students, this is an effort to form good student character in accordance with the concepts of the Koran and hadith. In its contribution, Islamic religious teachers approach students, Islamic religious teachers at Anuban Islam Songkhla School take an approach based on a communication process that refers to the principles of Islamic communication, this is a step to stimulate students at Anuban Islam Songkhla School so that they can be influenced and engaging in Koran reading activities at Anuban Islam Songkhla School.